Long-term outcomes of percutaneous coronary intervention versus coronary artery bypass grafting for unprotected left main coronary bifurcation disease in the drug-eluting stent era. Issue 10 (15th March 2012) - Chang, Kiyuk; Koh, Yoon-Seok; Jeong, Seung Hee; Lee, Jong-Min; Her, Sung-Ho; Park, Hun-Jun; Kim, Pum-Joon; Kim, Young-Hak; Chung, Wook-Sung; Yim, Hyeon-Woo; Park, Seung-Jung; Seung, Ki Bae
Abstract : Objectives: There are limited data on long-term outcomes (ie, beyond 4 years) for patients with unprotected left main bifurcation disease who underwent percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) in the drug-eluting stent (DES) era. This study therefore compared the treatment effects of PCI and CABG in unprotected left main bifurcation disease. Methods: 865 patients with unprotected left main bifurcation disease treated with either PCI using DES (n=556) or CABG (n=309) were evaluated between May 2003 and December 2009. PCI-treated patients were further categorised into simple stenting (n=360) or complex stenting (n=196). Results: Median follow-up was 4.2 years (IQR 2.9–5.2 years). After adjusting covariates with multivariate Cox hazard regression model and inverse probability of treatment weighting, the long-term cumulative rates of death (HR 0.95; 95% CI 0.62 to 1.45) or composite of death, Q-wave myocardial infarction, or stroke (HR 0.97, 95% CI 0.64 to 1.48) were not significantly different for patients undergoing PCI or CABG except for target-vessel revascularisation (TVR) (HR 4.42, 95% CI 2.39 to 8.18). The complex stenting group had similar long-term clinical outcomes compared with the simple stenting group except for TVR (HR 1.94, 95% CI 1.22 to 3.10). In further analysis with propensity score matching, overall findings were consistent. Conclusions: In patients with unprotected left main bifurcation disease, PCI using DES provides similar long-term (up to 5.2 years) clinical outcomes except for TVR compared with CABG. Complex and simple stenting yielded similar outcomes except for a higher TVR rate in complex stenting.